An Empirical Assessment of the Convergence Theory of the Solow Model - Akadiri, Seyi Saint (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
This study empirically investigates the convergence theory based on the perceived level of diversities in the economic development within the countries of the world. he estimation method employed for this research work is the cross-sectional regression analysis to measure convergence, using data of 1980 and 2010 for 50 selected countries. Data for the study were extracted and sourced from the World Bank development indicators database. From the empirical evidence, we discovered there is a reaction, or better put, a feedback relationship between growth and the initial GDP per capita. This implies that, country with low initial GDP per capita is farther away from their steady state and would grow faster than the countries with high initial GDP per capita but closer to their steady state. On the nexus between the growth and initial GDP per capita, the regression analysis revealed that, level of investment is a catalyst for growth. Hence, we infer that, the poor countries should enhance their level of investment (both in human and physical capital). The more the level of investment, the more would be the level of growth. The model exhibits a natural long-run relationship. This made us to know that, no matter the level of disparities and diversities between the poor countries and the richer ones today; the former would still grow and catches up with the latter. Keywords: Convergence, growth, GDP per capita, investment, economic development, cross sectional.

ÖZ : Bu çalışma değişik kalkınmışlık düzeylerindeki ülkeleri kullanarak Convergence Theoriyi test etmektedir. Bu amaçla 50 ülkeli bir Cross-Sectional regresyon kullanılmıştır. Veriler 1980 ve 2010 tarihlerini kapsamaktadır. Tüm veriler Dünya Bankası World Development Indicators verileridir. Regrtesyon sonuçları büyüme oranları ile başlangıç kişi başı gelir düzeyleri arasında bir ilişki olduğunu göstermektedir. Başlangıçta kişi başı gelir seviyesi düşük olan ülkeler daha hızlı büyümektedir. Sonuçlar ayrıca yatırımların ekonomik büyümeyi hızlandırıcı olduğunu göstermektedir. Dolayısıyla gelişmekte olan ülkeler fiziksel ve beşeri yatırımlara öncelik vermelidirler. Anahtar Kelimeler: Convergence, Ekonomik Büyüme, Kişi başı gelir, Yatırım, Ekonomik Kalkınmışlık, Cress-Sectional.
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2015. Supervisor: Assist. Prof. Dr. Çağay Coşkuner.
Keywords: Economics; Economic Growth and Development; Economic development - Mathematical models; Convergence; growth; GDP per capita; investment; economic development; cross sectional